The effectiveness of photomindset learning media based on discovery learning to enhance EFL student's critical thinking - Manurung, Sulastri; Yuri, Melani Putri; Yudani, Nadia Putri; Sembiring, Elisma; Pratiwi, Septiani Indah; Ghaisani, Fadhilah (Universitas Riau Kepulauan, 2025)
Students’ low English proficiency and critical thinking often stem from traditional language learning methods that do not encourage performance, creativity, or analytical abilities. Teachers play a vital role in cultivating these skills through meaningful and interactive learning experiences. This study investigated the effectiveness of using photomindset learning media based on a discovery learning method to enhance English as a Foreign Language (EFL) students' critical thinking skills. Employing a quantitative approach with a one-group pre-test post-test design, this study involved 33 first-grade students from a Junior High School in Batam, Indonesia, through purposive sampling. The research instrument was a test consisted 30 multiple-choice questions and one essay covering reading and writing section, validated by expert judgment, Pearson Product-moment and tested for reliability using Cronbach’s Alpha. A Paired-sample T-test revealed a significant difference between pre-test and post-test scores (a sig. (2-tailed) = 0.000 < 0.05). The finding demonstrates that using photomindset learning media based on discovery learning effectively enhances students’ critical thinking skills. This study contributes valuable insights into EFL teaching by demonstrating how integrating discovery learning with visual media can foster students’ analytical and problem-solving abilities. Future research should explore its impact on other English skills and involve a larger sample with a control group for broader comparisons.